Conflict-Generating Factors of Educational Activities in Higher Education: Principles and Methods of Monitoring - Georgiy P. Artemov; Andrei V. Aleinikov; Anna G. Pinkevich (National Research Mordova State University, 2018)
Introduction. The article explores the conflict-related nature of educational activity. Analysis of modern scientific literature in Russia has revealed the fragmented nature of the study of this issue and the lack of a methodological foundation for the development of effective and practical conflict management strategies and programmes for regulating the impact on conflict situations in the educational process. The purpose of the article is to develop a theoretical and methodological tool for conflict diagnosis of modern higher education institutions and a model for monitoring conflict factors in modern institutions of higher learning. Materials and Methods. The methodological basis of the study are fundamental principles of the current theory of organisational conflicts, the development of procedures and technologies for their resolution in the educational process, including management decisions making. The proposed model for monitoring educational activities was tested at St. Petersburg State University using quantitative and qualitative methods of research. Results. It is substantiated that conflicts arising during the implementation of educational activities can lead to serious negative consequences, the removal of which requires considerable resources and time. The main characteristics and classification of various types of conflicts in the implementation of educational activities are singled out, the conflict determinants of the educational process as well as the relationships between students and teachers are investigated. In the empirical part of the work, basic principles and methods for organising conflictological monitoring of educational activity and requirements for its instruments are proposed. The use of monitoring allows to obtain valid results of a real picture of conflicts as an essential component of the effective work of the university. Discussion and Сonclusions. A list of indicators has been determined, which makes it possible to assess the factors of conflict in the educational process. The authors make a conclusion about the need for conflict monitoring as an integral part of the management of the educational process, aimed at obtaining timely, relevant and objective information about conflict and conflict in higher education institutions and improving the quality of management. The results of the study will contribute to the development of specific solutions for the development of the education system as a tool for the formation of solidarity and socio-political stability values of modern Russian society.